Short Peripheral Intravenous Catheter-related Phlebitis in Patients with COVID-19: A Propensity Score-matched Study - Özge ÖZGEN TOP; Hasan Selçuk ÖZGER; Dane BURSA; Hatice ŞİMŞEK; Murat DİZBAY (Mediterranean Journal of Infection, Microbes and Antimicrobials, 2024)
Introduction: Peripheral intravenous catheters (PIVCs) are commonly used for intravenous therapy. A catheter is removed early when complications such as phlebitis develop. This study aimed to compare PIVC-related phlebitis, catheter dwell time, and insertion practices in patients with and without Coronavirus disease-2019 (COVID-19). Materials and Methods: This single-center, prospective study was conducted in patients hospitalized between January 24, 2022, and June 24, 2022. All catheters were grouped as phlebitis and non-phlebitis, and risk factors were compared. Patients with and without COVID-19 were matched for phlebitis risk factors and compared for the incidence of phlebitis and catheter dwell time. Results: A total of 932 catheters were followed up prospectively in 369 patients. Phlebitis developed in 21.8%. Poor skin elasticity, insertion shift (night shift), and antibiotic use were found as independent risk factors for phlebitis in the univariate and multivariate analyses. No difference in the incidence of phlebitis was found between patients with and without COVID-19, and no difference in phlebitis-free catheter dwell times was noted between the groups. Labor times for inserting PIVCs were significantly higher in patients with COVID-19 than in those without COVID-19 [median, 13.5 (10-15) vs. 5.0 (5-10) min, p<0.001]. Conclusion: Coronavirus disease-2019 did not increase the risk of PIVC-related phlebitis and did not directly affect phlebitis-free dwell time. Labor times for inserting PIVCs were significantly higher in patients with COVID-19 due to donning personal protective equipment. Although poor skin elasticity, insertion shift (night shift), and antibiotic use were found as independent risk factors, COVID-19 was not a significant risk factor for phlebitis. The results support the replacement of PIVCs in patients with COVID-19 when clinically indicated, whereas COVID-19 has no significant effect on catheter dwell times.